Collective Value-At-Risk (Colvar) In Life Insurance Collection - Talib Bon, Abdul; Iqbal Al-Banna Ismail, Muhammad; ., Sukono; Ronnie Effendie, Adhitya (International Journal of Engineering and Technology, 2018)
Analysis of risk in life insurance claims is very important to do by the insurance company actuary. Risk in life insurance claims are generally measured using the standard deviation or variance. The problem is, that the standard deviation or variance which is used as a measure of the risk of a claim can not accommodate any claims of risk events. Therefore, in this study developed a model called risk measures Collective Modified Value-at-Risk. Model development is done for several models of the distribution of the number of claims and the distribution of the value of the claim. Collective results of model development Modified Value-at-Risk is expected to accommodate any claims of risk events, when given a certain level of significanceÂ Â